2014
DOI: 10.2169/internalmedicine.53.2319
|View full text |Cite
|
Sign up to set email alerts
|

<i>Elizabethkingia meningoseptica</i> as an Unusual Pathogen Causing Healthcare-associated Bacteriuria

Abstract: Elizabethkingia meningoseptica is recovered from urine samples in very unusual cases, although the clinical significance of its detection remains unclear. Four cases of E. meningoseptica bacteriuria were analyzed, and E. meningoseptica was found to be the causative agent of healthcare-associated bacteriuria, including urinary tract infections, asymptomatic bacteriuria and transient bacteriuria, primarily in elderly patients with diabetes. Although E. meningoseptica cultured from urine was found to be resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Previous studies have reported that Elizabethkingia spp., which are Gram-negative bacteria, show excellent resistance to antibiotics, which may explain why patients are difficult to cure of these infections [3537]. We found that E. miricola mainly parasitizes the neurological organs, such as the brain.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported that Elizabethkingia spp., which are Gram-negative bacteria, show excellent resistance to antibiotics, which may explain why patients are difficult to cure of these infections [3537]. We found that E. miricola mainly parasitizes the neurological organs, such as the brain.…”
Section: Discussionmentioning
confidence: 90%
“…(Han and Andrade, 2005 ), Elizabethkingia spp. (Zong, 2014 ; Hagiya et al, 2015 ), and Methylobacterium spp. (Lee et al, 2004 ) that are increased in UUI have been associated previously with urinary tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the organism rarely results in a UTI (6). In previous cases of UTI caused by E. meningoseptica (7)(8)(9), all of the bacterial identifications were based on the biochemical properties of the isolated pathogens. In contrast, the isolate in the present case was confirmed to be E. meningoseptica by means of 16S rRNA sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, although there have been a few cases of E. meningosepticarelated UTIs (7)(8)(9), there have been no reports of nephrostomy-associated cases. We herein report the first case of post-nephrostomy perinephric abscess caused by an E. meningoseptica infection that occurred in a patient with idiopathic retroperitoneal fibrosis.…”
Section: Introductionmentioning
confidence: 99%